The Quality of Tofu Industry Wastewater in the Stabilization Ponds and the Effects of Discharged Waste in the Tarai River, Tambang Sub-Regency, Kampar - Wingga Novelizon; M. Hasbi; Budijono ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
A study aims to understand the condition of tofu industry waste water, the effectiveness of stabilization ponds in improving the waste water quality and the effects of discharged waste in the Tarai River, a study has been conducted on September 2016. The tofu waste was obtained from one of the tofu industry in the Tambang districts, Kampar. Wastewater was sampled from the stabilization ponds (3 sampling areas) and in the Tarai River (around 2m and 200m from the outlet and 50m before the outlet). Parameters measured were temperature, pH, TSS, BOD, COD and NH3. Results shown that the temperature decrease, from 33oC to 29.7oC, pH improved (5 to 7), BOD decreased (from 51.9 mg/L to 20.2 mg/L), COD decreased (from 2,550 mg/L to 900 mg/L, TSS decreased (from 40 mg/L to 17 mg/L) and NH3 improved (from 0.7 mg/L to 0.9 mg/L). The effectiveness of the ponds in decreasing the BOD5 was 16.1-85%, the COD was 50-76,9%, and the TSS was 50-75%. The treated tofu liquid waste that was discarded to the river slightly affects the river’s water quality.Keywords: tofu industry, wastewater, stabilization ponds, Tarai River